The impact of beta (ß) value in measuring social learning influence on the behaviour of Muslim adolescents - Ahmad Munawar Ismail,; Wan Kamal Mujani, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Social learning factor is a reflection of the numerous existing social environment factors. It exists in the environment together with human’s internal natural process and it may significantly affect human’s behavioural development. The impact can occur directly or indirectly. A human being will be found different based on the environment in which he or she is. Whoever finds himself in an environment and education that helps him towards goodness, then he is more likely to be a good group and vice versa. Therefore, a good environment is necessary to produce good morals. Now the development of the industrial revolution 4.0 dominates everything and also affects Muslim children in their social environment. This study focuses on the dominant factors in social learning which influence the behaviour of Malaysian adolescents. Five social environment factors are identified as being significant in the development of the adolescents’ behaviour; they are: parents, peers, teachers, artistes and school culture. This study which employs both quantitative method and survey involves 16-year-old respondents totalling 1504 from all over peninsula Malaysia. Data from this study are analysed both descriptively and statistically with the mean, standard deviation and double regression at (p<0.05). Results from the double regression analysis showed that the most dominant factor in moulding the behaviour of the adolescents is peers followed by school culture, parents, teachers and artistes. Even though the artistes’ factor is the least dominant, based on the Beta value, it may negatively affect the behavioural development compared to other social environment factors.